Social Work Students Beliefs Towards Mental Illnesses and the Effects of Theoretical Education About Mental Illnesses - Nalan KARA (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Beliefs towards mental illnesses of health workers and student candidates might be negative. In this study, determination of Social Work students beliefs towards mental illnesses and factors related to these beliefs and the effects of theoretical education about mental illnesses were aimed. Method: Twenty eight third-grade students studying at the Social Work Department of Turgut Ozal University were evaluated by sociodemographic form and Beliefs Towards Mental Illness Scale (BMI). Theoretical lectures about mental illnesses were given to the students 2 hours weekly for 14 weeks. At the end of the lectures, the students were given BMI again and the changes in their beliefs towards mental illnesses after the education were investigated. Results: The mean age of the students was 20.8±0.9, 78.6% (n=22) were female, 85.7% (n=24) never consulted a psychiatrist, 60.7% (n=17) reported no family member/relative/friend/neighbour with psychiatric disease. The students who consulted a psychiatrist had lower score in dangerousness subscale of BMI, however, the difference remained at the edge of the significance level (p=0.056). After the lectures, the scores of dangerousness subscale and total BMI decreased significantly (p [JCBPR 2015; 4(2.000): 69-77]